2021
DOI: 10.13187/ejced.2021.2.462
|View full text |Cite
|
Sign up to set email alerts
|

Developing Computational Thinking of Specialists of the Future Through Designing Computer Games for Educational Purposes

Abstract: The problem that the given paper aims to solve is associated with the need to resolve the contradiction between the requirements of the digital economy for a high level of computational thinking of specialists of the future and an insufficiently developed methodological base for training graduates that meets these requirements.The purpose of the research is to theoretically prove and experimentally verify the need for the use of gamification technology in training of specialists of the future to form computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
1
0
3
Order By: Relevance
“…For example, E. V. Soboleva et al showed that games and game-like elements are powerful tools that can be used to focus on learning [18]. The creation of mobile applications for language learning has led to the gamification of this sector: prizes, flash cards and other game features make learning a language informal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, E. V. Soboleva et al showed that games and game-like elements are powerful tools that can be used to focus on learning [18]. The creation of mobile applications for language learning has led to the gamification of this sector: prizes, flash cards and other game features make learning a language informal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Особенностью предлагаемого варианта организации учебно-проектной деятельности является то, что для разбиения учебной группы на команды применяется сервис «Колесо фортуны» 7 . Это интерактивная программа, позволяющая автоматизировать случайный выбора участника.…”
Section: под учебным проектом будем понимать организованную и направл...unclassified
“…Зенкиной, М.И. Бочарова [7] о дидактических возможностях современных интерактивных ресурсов в плане формирования востребованных навыков профессионалов будущего.…”
Section: под учебным проектом будем понимать организованную и направл...unclassified
See 1 more Smart Citation